1995
DOI: 10.1074/jbc.270.27.15966
|View full text |Cite
|
Sign up to set email alerts
|

Arginine 206 of the C5a Receptor Is Critical for Ligand Recognition and Receptor Activation by C-terminal Hexapeptide Analogs

Abstract: C5a is a 74-amino-acid glycoprotein whose receptor is a member of the rhodopsin superfamily. While antagonists have been generated to many of these receptors, similar efforts directed at family members whose natural ligands are proteins have met with little success. The recent development of hexapeptide analogs of C5a has allowed us to begin elucidation of the molecular events that lead to activation by combining a structure/activity study of the ligand with receptor mutagenesis. Removal of the hexapeptide's C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 22 publications
8
84
1
Order By: Relevance
“…For small agonistic peptides, an interaction of the C-terminal arginine with Arg 206 in the fifth transmembrane helix of the C5aR has been postulated (36). Also unknown is the molecular basis of the distinct bioactivity of C5a desarg .…”
Section: Discussionmentioning
confidence: 99%
“…For small agonistic peptides, an interaction of the C-terminal arginine with Arg 206 in the fifth transmembrane helix of the C5aR has been postulated (36). Also unknown is the molecular basis of the distinct bioactivity of C5a desarg .…”
Section: Discussionmentioning
confidence: 99%
“…C5a is a 74-amino acid glycoprotein that is liberated during complement activation and mediates such processes as neutrophil chemotaxis, platelet activation, and vascular permeability (21). Binding of C5a to its receptor involves a two-site binding model with the COOH terminus of the ligand inserting into the receptor interhelical crevice and other portions of the ligand interacting with the NH 2 terminus of C5aR to enhance ligand affinity (22). C5aR serves as a useful model to study GPCR oligomerization for two major reasons.…”
mentioning
confidence: 99%
“…Then, possible orientations of the entire structure of C5a were restored by overlapping the rigid core C5a-(1-62) from PDB entry 1KJS with each of the four selected orientations of C5a-(59 -74) within C5aR. It was found that only one specific orientation of C5a satisfied the requirements of spatial proximity of positions 15,18,19,20,27, and 46 in C5a to specific residues in the N-terminal segment 8 -41 of C5aR, as was suggested by available site-directed mutagenesis data (31,32). Seventeen conformations of NT 8 -41 (out of 185) and 11 conformations of the EC1 ϩ EC2 ϩ EC3 loop package (out of 29) did not show steric clashes with this particular orientation of C5a; all these conformations together with the selected orientation of C5a and the TM region of C5aR make up the final model of the C5a-C5aR complex.…”
Section: Methodsmentioning
confidence: 99%
“…3 The model was successfully utilized for rationalizing available site-directed mutagenesis data in the N-terminal fragment of C5aR (mutations involving Asp 15 , Asp 16 , Asp 21 , and Asp 27 (10,14)) as well as in C5a (mutations involving His 15 , Val 18 , and Arg 46 (32)). The model was also validated by comparison to the data on C5aR mutants E199K, D282R, R206A, and R175D (16, 18, 33-35).…”
Section: Use Of C5a C27r/r40c To Trap Interactions With the C5ar Nt-c5amentioning
confidence: 99%
See 1 more Smart Citation